ANALISIS PENGARUH KONTRAK PSIKOLOGIS, LEADER MEMBER EXCHANGE (LMX), DAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING TERHADAP KINERJA KARYAWAN (Studi pada karyawan Divisi Garmen 5 PT. Sri Rejeki Isman, Tbk.) - Dani Yonatan; Indi Djastuti (Faculty of Economics and Business Diponegoro University, 2018)
The purpose of this study is to analyse the effect of psychological contract, leader member exchange, and job satisfaction on employee performance. The population used in this study is the employees of Garment 5 Division PT Sri Rejeki Isman, Tbk. that have been an permanent employee with minimum tenure 2 years and minimum level of education is senior high school and its equivalent. The amount of sample used in this study is 150 respondent. Data collection using questionaires. This research uses structural equation modelling (SEM) analysis with AMOS 24.0 software as analysis tool.The result shows that psychological contract has a positive and significant effect on employee performance, leader member exchange has a positive and not significant effect on employee performance, psuchological contract has a positive and significant effect on job satisfaction, leader member exchange has a positive and not significant effect on job satisfaction and job satisfaction has a positive and significant effect on employee performance. This research also shows that there is no mediation effect of job satisfaction to the effect of psychological contract on employee performance.